2021
DOI: 10.1038/s41598-021-94295-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors, and prediction score of carbapenem resistance among inpatients colonized or infected with 3rd generation cephalosporin resistant Enterobacterales

Abstract: In this study, we determined the incidence and risk factors of Carbapenem-resistant Enterobacterales (CRE) acquisition in inpatients with 3rd generation cephalosporin-resistant (3GCR) Enterobacterales at a tertiary-care hospital in Lebanon, and suggested a risk prediction score for it. This is a retrospective matched case–control study of inpatients with 3GCR Enterobacterales that are carbapenem resistant (cases) versus those with carbapenem-sensitive isolates (controls). Data analysis was performed on IBM SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Antibiotic resistance is a global health concern requiring concerted efforts for its control ( 1 , 2 ). Gram-negative bacteria have become resistant to a wide spectrum of antibiotics mainly as a consequence of structural adaptations and production of enzymes, such as extended spectrum beta lactamases (ESBLs) and carbapenemases, that inactivate antibiotics ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance is a global health concern requiring concerted efforts for its control ( 1 , 2 ). Gram-negative bacteria have become resistant to a wide spectrum of antibiotics mainly as a consequence of structural adaptations and production of enzymes, such as extended spectrum beta lactamases (ESBLs) and carbapenemases, that inactivate antibiotics ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies failed to show that age may be associated with CRE BSI. 27,28 However, this study found that age was one of the independent risk factors included into the prediction model, The differences listed above might be explained by the fact that previous studies were focused on children or adult patients of a certain age. In addition, prior antibiotic treatment was not significantly associated with BSI in our study, while previous studies found that tigecycline use before admission was associated with BSI.…”
Section: Discussionmentioning
confidence: 69%
“…Enterobacterales are an important cause of serious infections [ 16 , 17 ]. Many bacteria belonging to this family are now becoming increasingly resistant to existing antibiotics [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%